2018
DOI: 10.1155/2018/3275284
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of Thulium Doped Fiber Laser in Pig Model of Liver Surgery

Abstract: Partial liver resection is a treatment of choice for liver tumors; the range of parenchyma excision varies from a small part of the tissue surrounding the neoplasm up to 70% of the organ. One of the major concerns during liver resection is blood loss. Thulium lasers which are characterized by the length of emission wave corresponding to a peak absorption of water create a new possibility of cutting tissues efficiently with minimal thermal damage and concurrently providing a good hemostasis control. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Maciej et al states that TDFL had a very good cutting properties while the total depth of thermal changes in the liver tissue ranges from 0.62 to 1.82 mm depending on the time of evaluation. Similar width of the thermal damage zone (less than 2.0 mm) was reported in an experimental pig model for partial nephrectomy with TDFL [ 12 , 19 , 20 ]. TDFL also has potent local thermal effect resulting in its ability to cut and coagulate, thus providing hemostasis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Maciej et al states that TDFL had a very good cutting properties while the total depth of thermal changes in the liver tissue ranges from 0.62 to 1.82 mm depending on the time of evaluation. Similar width of the thermal damage zone (less than 2.0 mm) was reported in an experimental pig model for partial nephrectomy with TDFL [ 12 , 19 , 20 ]. TDFL also has potent local thermal effect resulting in its ability to cut and coagulate, thus providing hemostasis.…”
Section: Discussionsupporting
confidence: 78%
“…Maciej et al, showed the efficacy of TDFL in cutting with a narrow zone of thermal injury and provides good hemostasis during partial liver resection and liver tissue incision. TDFL operating at 1940 nm may be a potential tool in oncologic liver surgery, especially when healthy tissue sparing is a priority and small atypical excisions are performed [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The beam quality for the output radiation was of high quality, allowing for its use in thin treatment probes (less than 50 µm in diameter). The design and detailed physical parameters of the laser have been described in detail elsewhere [8,26,27].…”
Section: Lasersmentioning
confidence: 99%
“…Kidney fragments were prepared as described previously [26,27]. Briefly, excised fragments and portions of the organ at the site of excision were fixed in 10% buffered formaldehyde solution and then cut into small blocks transversely to the cutting line and embedded in paraffin.…”
Section: Microscopic Evaluationmentioning
confidence: 99%
“…A fiber laser with an active medium in the form of a thulium-doped (Tm 3+ ) optical fiber (TDFL) working at a wavelength of 1940 nm shows nearly 1000 times greater absorption by water when compared with lasers emitting light at 1064 nm (Nd: YAG laser). This feature enables precise tissue ablation with a small margin of coagulation, while laser radiation of a 1064 nm wavelength penetrates deeper into tissue with less controlled coagulation effects [16][17][18].…”
Section: Introductionmentioning
confidence: 99%